2023
DOI: 10.1186/s41938-023-00680-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a native entomopathogenic nematode Heterorhabditis bacteriophora (isolate Z-1) against potato tuber moth (Phthorimaea operculella (Zeller) (Lepidoptera: Gelechiidae) in Turkey

Abstract: Background Potato tuber worm (PTM) [Phthorimaea operculella (Zeller) (Lepidoptera: Gelechiidae)] is one of the most significant and widespread pests of potato. PTM damages potatoes both in the field and in potato storage areas. Control of the pest is getting harder as it is developing resistance to pesticides. Several entomopathogenic nematode (EPN) species have been reported to successfully control numerous agricultural pests worldwide. The main aim of the study was to isolate native nematode/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Also, Abd El-Motaalet al (2021) found that the mortality rate increased as the concentration of IJs increased. In Turkey, a recent study by Barış et al (2023) indicated that the last instar larvae of Ph. operculellawere highly susceptible to native EPN H. bacteriophora (isolate Z-1), as well as larvae and pupae mortalities increased with the increasing concentration of EPN.…”
Section: I2 Correlation Of the Insect Mortality With The Epn Concentr...mentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Abd El-Motaalet al (2021) found that the mortality rate increased as the concentration of IJs increased. In Turkey, a recent study by Barış et al (2023) indicated that the last instar larvae of Ph. operculellawere highly susceptible to native EPN H. bacteriophora (isolate Z-1), as well as larvae and pupae mortalities increased with the increasing concentration of EPN.…”
Section: I2 Correlation Of the Insect Mortality With The Epn Concentr...mentioning
confidence: 99%
“…Pupae of L. vanillana were less susceptible than larvae to the infection with S. yirgalemense and S. jeffreyense (Du Preez et al, 2021). Recently, Barış et al (2023) indicated that the last instar larvae of Ph. operculellain Turkey were highly susceptible to native H. bacteriophora (isolate Z-1).…”
Section: Susceptibility Of Pupal Stagementioning
confidence: 99%
“…Control of the pest is increasingly difficult as it develops resistance to pesticides. Several entomopathogenic nematode species (EPN) have been reported to successfully control numerous agricultural pests worldwide (Barış et al, 2023).…”
Section: Introductionmentioning
confidence: 99%